Care burden, perceived social support, coping attitudes and life satisfaction of mothers with children with cerebral palsy - Dertli, Semiha; Aydin (Yilmaz), Aydan Selen; Gunay, Ulviye (Wiley, 2024)
Aim: This study's aim is to determine the relationship between care burden, perceived social support, coping attitudes and life satisfaction of mothers with children with cerebral palsy (CP). Methods: This descriptive study was conducted in Turkey between March and June 2022 to determine the relationship between caregiving burden, perceived social support, coping attitudes and life satisfaction of 122 mothers with CP children. Path analysis was used to evaluate the data. Results: Correlation analysis showed a positive relationship between mothers' social support perceptions and life satisfaction and coping attitudes, a positive relationship between their life satisfaction and coping attitudes (p < .001). The path analysis showed that the social support perceived by the mothers significantly affected their coping attitudes (beta = .257; p < .001) and life satisfaction (beta = .081; p < .001). Mothers' care burden (beta = .169; p < .001) and coping attitudes (beta = .071; p < .05) also had a significant effect on their life satisfaction. Conclusions: It is an important finding of this study that mothers' perceptions of social support and coping attitudes have a positive effect on their life satisfaction. Long-term care can cause physical and psychological problems for mothers. Mothers' strong coping strategies and high levels of social support may reduce the occurrence of these problems. Drawing attention to this issue in mothers and revealing the effects of these variables is important in terms of indirectly supporting child outcomes.
Keywords: care burden; coping attitude; life satisfaction; mother of a child with cerebral palsy; perceived social support